Tuning the contact conductance of anchoring groups in single molecule junctions by molecular design. Issue 27 (1st July 2019) - Šebera, Jakub; Lindner, Marcin; Gasior, Jindřich; Mészáros, Gábor; Fuhr, Olaf; Mayor, Marcel; Valášek, Michal; Kolivoška, Viliam; Hromadová, Magdaléna
Abstract : Molecular design allows tuning of the contact conductance of anchoring groups in single molecule junctions. Abstract : A tetraphenylmethane tripod functionalized with three thiol moieties in the para position can serve as a supporting platform for functional molecular electronic elements. A combined experimental scanning tunneling microscopy break junction technique with theoretical approaches based on density functional theory and non-equilibrium Green's function formalism was used for detailed charge transport analysis to find configurations, geometries and charge transport pathways in the molecular junctions of single molecule oligo-1, 4-phenylene conductors containing this tripodal anchoring group. The effect of molecular length ( n = 1 to 4 repeating phenylene units) on the charge transport properties and junction configurations is addressed. The number of covalent attachments between the electrode and the tripodal platform changes with n affecting the contact conductance of the junction. The longest homologue n = 4 adopts an upright configuration with all three para thiolate moieties of the tripod attached to the gold electrode. The contact conductance of the tetraphenylmethane tripod substituted by thiols in the para position is higher than that substituted in the meta position. Such molecular arrangement is highly conducting and allows well-defined directional positioning of a variety of functional groups.